Discipleship In The Concept Of Power Ministry Based On The Kingdom Of God - Tonny Andrian (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
Discipleship is undeniably the psychomotor of the church as well as the application of the Great Commission of the Lord Jesus Christ. The Lord Jesus Himself did discipleship which started with 12 disciples as well as 70 disciples. Likewise with the life of the Apostles, there were Paul, Silas, Timothy and Titus, where they became messengers of Christ Jesus the Lord preaching about the Kingdom of Heaven. The kingdom of heaven gave birth to the church. So the youth with the concept of the kingdom of heaven should be a bridge for the millennial generation. Millennials tend to be: Multitasking (working with a variety of activities), Collaboration (strong collaboration skills), Transparency (openness in many fields), balance of work and way of life (healthy ways of life and nutritious intake), Tech savvy that is concerned with the latest technology / updates status, connected in social media, hard worker, concerned with job satisfaction. Reaching the end of the concept of discipleship with power of ministry based on the kingdom of heaven has not been as expected unto the millennial generation in life will become a strong generation with a mentality that is more than a winner with the power of the Lord Jesus working in their lives. They live under free sex, drugs and pornography ect. How can we as a leader to disciple them and knowing heavenly Father to become a millennial generation who have dignity and are directed towards the glory of God.